Global Financial Stability Report, September 2004 : Market Developments and Issues. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2004)
This September 2004 issue of the Global Financial Stability Report highlights that over the past six months, the global financial system, especially the health of financial intermediaries, has been further strengthened by the broadening economic recovery. The financial system has not looked as resilient as it does in the summer of 2004, in the three years since the bursting of the equity bubble. Financial intermediaries, banks and nonbanks alike, have strengthened their balance sheets to a point where they could, if necessary, absorb considerable shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet